2008
DOI: 10.1002/app.28766
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prior aging at 288°C in air and in argon environments on creep response of PMR‐15 neat resin

Abstract: The creep behavior of PMR-15 neat resin, a polyimide thermoset polymer, aged in air and in argon environments at 2888C for up to 1000 h was evaluated. Creep tests were performed at 2888C at creep stress levels of 10 and 20 MPa. Creep periods of at least 25-h in duration were followed by 50-h periods of recovery at zero stress. Prior isothermal aging increased the elastic modulus and significantly decreased the polymer's capacity to accumulate creep strain. The aging environment had little influence on creep an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…We also note that we chose the functions for the material moduli (μ p ,μ G ,η) such that they increase as α goes from 0 to 1. This is consistent with the experiments (see figure 5 in Ruggles-Wrenn and Broeckert (2009)) where it seen that the elastic modulus increases with aging. We further note that such a choice of functions for the material moduli is different from what Rajagopal et al (2007) have chosen in their work.…”
Section: Constitutive Assumptionssupporting
confidence: 93%
“…We also note that we chose the functions for the material moduli (μ p ,μ G ,η) such that they increase as α goes from 0 to 1. This is consistent with the experiments (see figure 5 in Ruggles-Wrenn and Broeckert (2009)) where it seen that the elastic modulus increases with aging. We further note that such a choice of functions for the material moduli is different from what Rajagopal et al (2007) have chosen in their work.…”
Section: Constitutive Assumptionssupporting
confidence: 93%
“…Figure 2 presents the tensile stress–strain curves obtained at strain rates of 10 −6 and 10 −4 s −1 for the unaged material and for specimens aged for 100, 250, and 1000 h. It is seen that the elastic modulus increases with prior aging time. The effect of prior aging on the elastic modulus, which is further illustrated in Figure 3, is consistent with the observations reported earlier 19. Furthermore, stress–strain curves in Figure 2 show that for a given strain rate the departure from quasi‐linear behavior occurs at higher stress levels for specimens subjected to longer prior aging times.…”
Section: Experimental Observationssupporting
confidence: 89%
“…The PMR‐15 neat resin panels were manufactured and postcured by HyComp Inc. (Cleveland, OH). The details of the PMR‐15 chemistry and processing, as well as the schematic of the free standing postcure cycle are given elsewhere 19, 20. Dogbone shaped test specimens of 150‐mm total length with a 7.6‐mm wide gage section were machined from the 3.18‐mm thick panels using diamond‐grinding.…”
Section: Materials and Experimental Arrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of long time aging of polyimide at high temperature (>200 °C) and in oxidative environment on the mechanical properties [39], weight loss [40,41], and chemical properties [42,43], was widely investigated for thick polyimide matrix composites (1 mm thick) used in high temperature aerospace applications. It was found that while thermal degradation occurred throughout the material, the oxidative degradation occurs mainly within a thin surface layer where oxygen diffuses into the material.…”
Section: Thermal Aging Of Bpda-pda Polyimidementioning
confidence: 99%